Optimasi Analisa Karateristik Penurunan Decline Curve Sumur X Model Dual Segment Berbasis Sum Square of Error - Yedi Saputra Junior; Algi Setiawan; Elfisius Geron (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Reservoir pressure depletion in mature fields causes an unavoidable decline in natural production rates. This study applies the Dual Segment Decline Curve Analysis (DCA) method based on Sum of Squared Errors (SSE) optimization to Well X to minimize the subjectivity of visual history matching. The minimum error evaluation results indicate that the optimum decline parameters for Segment 1 follow a hyperbolic curve ( ; SSE of 13,933,517) and Segment 2 follows an exponential curve ( ; SSE of 3,626,637). This dual-segment model proves highly valid and accurate in representing production fluctuations and the effects of mechanical well interventions. Long-term forecasting projections up to the economic limit yield an Estimated Ultimate Recovery (EUR) of 30.2881 MMSTB for Segment 1 (cumulative production of 29.53543 MMSTB; remaining reserves of 0.75267 MMSTB) and reach 31.34472 MMSTB for Segment 2 ( of 31.13125 MMSTB; of 0.21347 MMSTB).